Bacteriology of humans - Wilson, Michael (Malden, MA : Blackwell Pub., 2008)
"Until recently, the indigenous microbiota of humans has been a relatively neglected area of microbiology, with most attention being focused on those microbes that cause disease in humans, rather than on those that co-exist with us in the disease-free state. However, in the past decade research has shown that not only is the indigenous microbiota involved in protecting humans from exogenous pathogens but it also plays an important role in our development and contributes to our nutritional and energy requirements. Consequently, interest has grown substantially among health professionals and scientists in analyzing and understanding these microbial (largely bacterial) communities." "This comprehensive yet accessible text provides an up-to-date guide to the development, composition, and distribution of indigenous microbial communities of humans. With the aid of abundant color figures, diagrams, tables, and maps, it establishes links between the physiocochemical and biological factors prevailing at an anatomical site and the types of microbes to be found there. The book includes an introduction to the human-microbe symbiosis as well as an in-depth look at the main systems and organs of the human body that have an indigenous microbiota. Each chapter includes a list of references for further study." "This is an excellent and informative reference book that will be useful to anyone with an interest in microbiology, medical microbiology, microbial ecology, infectious diseases, immunology, human biology, medicine, dentistry, nursing, health sciences, biomedical science, or pharmacy: it should be on the shelf of every major science and medical library."--BOOK JACKET.
The human-microbe symbiosis -- The indigenous microbiota of the skin -- The indigenous microbiota of the eye -- The indigenous microbiota of the respiratory tract -- The indigenous microbiota of the urinary system of females -- The indigenous microbiota of the reproductive system of females -- The indigenous microbiota of the urinary and reproductive systems of males -- The indigenous microbiota of the oral cavity -- The indigenous microbiota of the gastrointestinal tract -- The future.
Keywords: Human body; Microbial ecology; Humans; Bacteriology